Investigations on Apoptotic Activities of Cherry Laurel Extracts in HCT-116 Human Colon Carcinoma Cells - (:unkn) unknown (ASSOC PHARMACEUTICAL TEACHERS INDIA, 2019)
Background: Cherry laurel fruits are characterized by their dark color and rich phenolic contents. Previously, phenolic extracts from cherry laurel varieties were shown to demonstrate anti-proliferative activities against cancerous cell lines. Aim: To characterize the phenolic compound content of cherry laurel varieties since their characterization is incomplete and determine their apoptotic potential. Methods: The phenolic compounds of fruit extracts from 3 different cherry laurel varieties were analyzed using an LC-MS/MS method. Using flow cytometry, apoptotic activities of cherry laurel extracts were studied against HCT-116 human colon carcinoma cells. Results: 14 different phenolic compounds were qualitatively determined, whereas for 5 compounds quantitation was possible. To the best of our knowledge, the presence of epicatechin, epigallocatechin, quercetin, quercetin-3-glucoside, procyanidin B2, delphinidine-3-O-rutinoside, delphinidine-3-O-glucoside, cyanidine-3-O-glucoside and cyanidine-3-O-rutinoside is being reported for the first time for these extracts. Although some dependence on phenolic profile and concentration was obvious, in most cases, a significant extent of apoptotic induction (40-60%) was observed against HCT-1 16 cells. Conclusion: Findings on anti-proliferative and apoptotic activity verified the anti-carcinogenic capabilities of cherry laurel extracts.
Keywords: Cherry laurel; Phenolic compounds; How cytometry; Apoptosis; LC-MS/MS analysis; Anthocyanins; IN-VITRO; CANCER CELLS; CYCLE ARREST; ANTIOXIDANT; POLYPHENOLS; GROWTH; ANTHOCYANINS; EXPRESSION; DEATH; ACID